The Indonesian Government's Economic Policy During the Pandemic: A Study of Legal Protection for Debtors Affected by Covid-19 - Wahyuni, Sri (UIN Sunan Kalijaga, 2022)
Abstract: This article discusses government policies to protect debtors affected by Covid-19 and its implementation in banking institutions. This article used a juridical-empirical approach with the theory of default, overmatch, and hardship. This article collects data sources from some legislations and government policies during the Covid-19 pandemic and some credit institutions’ policies and debtors affected by Covid-19. This article reveals that the government has made a policy requiring creditors of banking financial institutions to relax credit for creditors affected by Covid-19, as contained in POJK Number 11/OJK.3/2020. With this policy, financial institutions can restructure credit for debtors. Due to difficult circumstances, the debtor who does not pay the credit installments in the credit agreement is no longer a default. They also cannot be subject to sanctions or demanded compensation for their inaccuracies in fulfilling their responsibility to pay installments. The government made a policy to provide legal protection for debtors affected by Covid-19. Abstract: Artikel ini membahas tentang kebijakan pemerintah dalam upaya melindungi debitur terdampak Covid-19 dan implementasinya pada lembaga perbankan. Artikel ini menggunakan pendekatan yuridis-empiris dengan memanfaatkan teori wan prestasi, overmacht dan keadaan sulit (hardshup). Data digali dari sejumlah peraturan perundang-undangan dan kebijakan pemerintah di masa pandemi Covid-19 dan juga sejumlah kebijakan lembaga kredit serta para debitur terdampak Covid-19. Artikel ini mengungkap bahwa pemerintah membuat kebijakan yang mengharuskan para kreditur lembaga-lembaga keuangan perbankan melakukan relaksasi kredit bagi para debitur terdampak Covid-19. Hal ini termuat dalam POJK Nomor 11/OJK.3/2020. Dengan adanya kebijakan ini, lembaga-lembaga keuangan dapat melakukan resktrukturisasi kredit bagi para debitur terdampak Covid-19. Para debitur yang tidak membayar angsuran kredit sesuai dengan perjanjian kredit yang telah dibuat tidak lagi dikatakan sebagai sebuah wanprestasi, karena adanya keadaan sulit (hardship). Mereka juga tidak dapat dikenai sanksi atau dituntut ganti rugi atas ketidaktepatannya dalam memenuhi tanggung jawabnya membayar angsuran. Kebijakan pemerintah tersebut dibuat dalam rangka memberikan perlindungan hukum terhadap para debitur terdampak Covid-19.